PERAN PRAKTIK KERJA LAPANGAN MAHASISWA JURUSAN ILMU PERPUSTAKAAN DALAM MENUNJANG PROGRAM PELESTARIAN KOLEKSI DI PERPUSTAKAAN FAKULTAS ADAB DAN HUMANIORA UIN ALAUDDIN MAKASSAR - Uliyana, Uliyana; Zhafirah Az-Zahra; A. Nur Annisa; Kasmaul Mar’a; Nurhalisa Nurhalisa; Irvan Muliyadi; Touku Umar; Saenal Abidin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Several collections in the Faculty of Adab and Humanities library are beginning to show signs of damage due to age, environmental factors, and user usage. This study aims to describe the role of students participating in Field Work Internships (PKL) in the Department of Library Science in supporting the library's collection preservation program. The method used was qualitative with a descriptive approach. The results indicate that the PKL students carried out a series of planned preservation activities, including: identifying and selecting damaged collections, checking and creating classification labels, simple physical repairs (such as hemming), packaging collections, inputting bibliographic data into the SLiMS system, and arranging collections on shelves. The implementation of these activities has been proven not only to extend the useful life of collections and maintain the integrity of their information, but also to significantly improve the quality of library services by making collections easier to find, neatly organized, and well-cataloged. Thus, the PKL program plays a strategic role in supporting collection preservation and the effectiveness of library services for users.